A proposed benchmark guide for customer engagement rating via YouTube channels - Osama Ahmed Abdelkader (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
YouTube is the biggest video platform to promote contents on the largest scale, but this does not mean that it will be available to 2 billion active users of this platform, as well viewers may not engage positively with published content at times. Therefore, Marketers need an applicable benchmark to assess the extent of the customer engagement rate CER with the content they broadcast, more than just monitoring numbers of views, likes and comments. This study aims to provide a proposed benchmark guide for CER with contents published via YouTube channels. The methodology of current paper follows both quantitative and qualitative methods, through collecting and analysing real data for 240 videos, representing a total of 5 videos from each one of the top 3 channels from each one of the 16 categories on YouTube (5*3*16=240). The result includes examine the differences in CER according to categories and countries. It also includes measuring how CER is impacted by video length, channel' experience years, and the numbers of subscribers and uploads. The article provides a set of recommendations that are expected to benefit academics and practitioners belong to marketing and social media in general, especially those interested in promoting content on the YouTube, and it suggests a group of future studies in this field.